Placental trophoblast syncytialization potentiates macropinocytosis via mTOR signaling to adapt to reduced amino acid supply - Xuan Shao; Guangming Cao; Dunjin Chen; Juan Liu; Bolan Yu; Ming Liu; Yu‐xia Li; Bin Cao; Yoel Sadovsky; Yanling Wang (2021)
Significance The appropriate allocation of nutrients between the mother and the fetus during pregnancy is predominantly governed by the syncytiotrophoblast lining at the outer surface of the placental villi. To date the advantages of such an extensively multinucleated cellular structure in substance exchange remains poorly understood. In this study, we discovered that differentiation of trophoblasts toward syncytium triggers an endocytosis strategy, macropinocytosis, to uptake large extracellular molecules. The unique uptake machinery is strikingly boosted via inhibition of mammalian target of rapamycin signaling under amino acid shortage conditions, which is essential for fetal survival. The findings highlight an adaptive mechanism of syncytiotrophoblast that senses nutrient status and support fetal survival under nutrient deprivation.